Tomar la cooperación descentralizada en serio, o la crónica de un difícil equilibrio entre la política y las políticas públicas - Hernández Ferreiro, Carlos (Revista Española de Desarrollo y Cooperación, 2023)
Decentralised Aid is a major feature of the Spanish System for International Cooperation. Yet, local and regional authorities are finding several obstacles to comply with the new international agenda for Development Co-operation as established in the so-called Monterrey Consensus and the París Declaration on Aid Effectiveness. This article argues that, only through a major process of redefinition of its political value, it might be possible to restructure the role of decentralized aid as a public policy in the context of the international fight against poverty.